Peningkatan Perkembangan Bahasa melalui Pembiasaan Berbahasa Jawa Krama pada Anak Usia Dini di RA Masyithoh 1 Parakan - Puti, Anindita Regina; Nasihin, Husna; Hastuti , Asih Puji (CV. Kurnia Grup, 2024)
The use of the Javanese language Krama upholds polite behavior in society. This research aims to determine the strategies and results of progress in language development in early childhood at RA Masyithoh 1 Parakan. The background to this research is that there are children who always use Ngoko language when talking to older people, teachers and parents. This research uses a qualitative approach and the type of research used is field research. The subjects in this research were five students attending RA Masyithoh 1 Parakan who always used ngoko language to speak to their elders. Determining the sample in this study used a purposive sampling technique. Research at RA Masyithoh 1 Parakan shows that the strategy of increasing early childhood language development through familiarization with Javanese Krama as the language of education is effective. The main supporting factors are the role of teachers who regularly use Javanese Krama, adequate school facilities, and support from parents who use Javanese Krama at home. The main obstacle is the use of the Ngoko language among peers and the family environment. As a result, one child showed improvement in understanding Javanese Krama, but could not yet speak it, while the other four students were able to speak Javanese Krama.